Preparation process of carrier-free lutetium-177

By using small-grain silica gel or polymer microspheres with uniform particle size as separation medium and combining aminocarboxylic acid-type chelating adsorbent, the efficient preparation of supportless letetium-177 was achieved, and the problems of low column efficiency, insufficient selectivity and complex production process in the prior art were solved, and the preparation of high concentration and high purity and simplification of the process was achieved.

CN119913378AActive Publication Date: 2025-05-02DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510402465.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-05-02
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

The existing carrier-free tertium-177 preparation process has problems such as low column efficiency, insufficient selectivity and complex production process, resulting in long separation time, long production time and high equipment corrosion.

Method used

Small-grain silica gel or polymer microspheres with uniform particle size distribution are used as separation media, combined with amino carboxylic acid-type chelating adsorbent for desalting of letetium. Through liquid chromatography separation, letetium desalting concentration and ytium desalting recovery, high-efficiency preparation of high-concentration and high-purity carrier-free letetium-177.

Benefits of technology

The efficient preparation of lete-177 is achieved, and a single separation column can achieve efficient preparation of trace lete-177, shortening the separation time, reducing radiation loss, simplifying the separation process, and reducing the factory design requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913378A_ABST
    Figure CN119913378A_ABST
Patent Text Reader

Abstract

The invention provides a preparation process of carrier-free lutetium-177, and belongs to the technical field of rare earth element extraction, the method comprises the following steps: obtaining a solution to be treated which contains lutetium element and ytterbium element and has a pH value less than or equal to 3; the method comprises the following steps: loading a to-be-treated solution to a separation column by taking an organic carboxylic acid solution as a mobile phase and a chromatographic filler with the surface modified with a sulfonic acid group as a stationary phase, and carrying out liquid chromatographic separation to obtain a lutetium fraction and an ytterbium fraction; adjusting the pH value of the lutetium fraction to 1-3 to obtain a lutetium-containing acid solution; injecting the lutetium-containing acid liquor into a lutetium desalination column, adsorbing lutetium ions in the lutetium desalination column, and then sequentially carrying out leaching and diluted hydrochloric acid elution to obtain a concentrated lutetium chloride solution; the lutetium desalination column is a chromatographic column taking an aminocarboxylic acid chelating agent as a stationary phase. High-concentration and high-purity lutetium chloride and ytterbium chloride are obtained through the steps of target material dissolving, ytterbium and lutetium separation, lutetium desalination and concentration, ytterbium desalination and recovery and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth element extraction, and in particular relates to a carrier-free lutetium-177 preparation process, which can be used in nuclear medicine, for treatment and / or diagnosis purposes. Background Art

[0002] Lutetium-177 ( 177 Lu) is a low-energy β-nuclide with a half-life of 6.7 days. It has the advantages of relatively long half-life, easy labeling of drug molecules such as antibodies and peptides, low β-ray energy, and short range in tissues. It is one of the most promising and market-dynamic integrated targeted radiotherapy nuclides.

[0003] at present, 177 Lu can be directly processed by nuclear reaction ( 176 Lu(n,γ) 177 Lu) or indirect method ( 176 Yb(n,γ) 177 Yb→ 177 Lu), the direct method ultimately produces a carrier 177 Lu; the indirect method obtains the carrier-free 177 Lu. There is a large amount of stable Lu-176 isotope in the Lu-177 prepared by the direct method. 177 The specific activity of Lu is low, which is not conducive to the subsequent labeling of monoclonal antibodies, peptides and other targeted drugs, thus affecting the diagnosis and treatment effect. 177 Lu has high specific activity and long half-life 177m Lu, impurity content is extremely low, and the absence of a carrier reduces the amount of the labeled compound precursor and increases the effective period of the nuclide labeling. However, the carrier-free 177 Lu is actually 176 Yb / 177 Lu mixture, the two need to be separated to obtain high-purity, high-specific-activity carrier-free 177 Lu.

[0004] The existing preparation processes of unsupported lutetium-177 mainly include chromatography, electrochemical method and sodium amalgam method. Among them, because chromatography has a strong separation ability and can distinguish substances with slight differences, it has a large separation coefficient for heavy lanthanide elements lutetium and ytterbium with similar chemical properties. Therefore, it is the main method currently used in actual production. However, the coarse granular resins used are hundreds of microns and have a wide particle size distribution. They belong to medium and low pressure chromatography, and have problems such as low column efficiency and insufficient selectivity, and the separation takes a long time. Invention patent applied by ITM Isotope Technology Munich AG: Production of high-purity unsupported 177 Lu compounds and methods without carrier addition 177Lu compound (publication number CN103718250A) uses four cation exchange chromatography columns in series for two-stage separation, and a single separation requires more than 220 minutes; the invention patent applied for by Zhejiang University Quzhou Research Institute: a method for separating and purifying carrier-free lutetium-177 (publication number CN118668079A), using leaching resin as chromatographic filler, also requires two separations, and the purity of lutetium obtained is 80%, and a single separation takes 10-20 hours. In addition, after the ytterbium-lutetium separation is achieved by ion exchange chromatography, post-treatment is required to remove the organic carboxylic acid introduced in the separation process to meet medical requirements. In the current technology, sulfonic acid resin is used as the post-treatment material, strong acid is used as the eluent, and then the strong acid is further evaporated to dryness; due to the strong corrosiveness of the strong acid, it has high requirements for the production plant and equipment, and this step also increases the production process and production time. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a preparation process of carrier-free lutetium-177, aiming to solve at least one technical problem in the background technology.

[0006] The present invention is achieved in that: A preparation process of carrier-free lutetium-177, comprising the following steps: Obtaining a target material to be separated which contains lutetium (including lutetium-177 isotope) and ytterbium and has a pH value of less than or equal to 3; An organic carboxylic acid solution is used as a mobile phase, a chromatographic filler with a surface modified with a sulfonic acid group is used as a stationary phase, a target material to be separated is loaded into a separation column, and liquid chromatography is performed to separate the target material into a lutetium fraction and an ytterbium fraction; The pH value of the lutetium fraction is adjusted to 1-3 to obtain a lutetium acid solution; The lutetium acid solution is injected into a lutetium desalting column, lutetium ions are adsorbed in the lutetium desalting column, and then eluted with dilute hydrochloric acid in sequence to obtain a concentrated lutetium chloride solution; the lutetium desalting column is a chromatographic column with an aminocarboxylic acid type chelating adsorbent as a stationary phase.

[0007] Furthermore, the specific operation of separating the lutetium fraction and the ytterbium fraction by liquid chromatography is: Use the mobile phase to flush the separation column so that the packing reaches an equilibrium state; The injector injects the target material solution into the quantitative loop; The target material to be separated in the quantitative ring enters the separation column driven by the mobile phase and begins to separate. The lutetium fraction and the ytterbium fraction flowing out of the separation column are respectively collected by detecting signals through an energy spectrum detector and / or an ultraviolet detector.

[0008] Furthermore, the preparation method of the target material to be separated is: using the ytterbium oxide-lutetium mixture obtained after reactor irradiation as a solid target material, adding one or more strong acid solutions of 0.5 mol / L~12 mol / L nitric acid, hydrochloric acid, sulfuric acid or hydrofluoric acid to completely dissolve it, adjusting the pH to 0~3 to meet the chromatographic loading requirements, and obtaining a mixture of ytterbium ions and lutetium ions as the target material to be separated.

[0009] Furthermore, the organic carboxylic acid is selected from at least one or more of lactic acid, α-hydroxyisobutyric acid, 2-hydroxy-2-methylbutyric acid, citric acid, ethylenediaminetetraacetic acid or their salts, and its concentration range is 0.01 mol / L~0.6 mol / L.

[0010] Further, the specific steps of obtaining a concentrated lutetium chloride solution include: Pumping deionized water into the lutetium desalting column to completely replace the solution inside the column; Add 0.1 mol / L to 12 mol / L hydrochloric acid or nitric acid to the lutetium fraction to adjust its pH to 1 to 3, and mix the two evenly by gas stirring; The lutetium fraction is transported to the lutetium desalting column by gas pressure or liquid pumping to provide power, and the lutetium ions are adsorbed in the filler; Deionized water was pumped into the lutetium desalting column for washing to remove residual organic carboxylic acids; Pump 0.05~0.5mol / L dilute hydrochloric acid into the lutetium desalting column, elute the adsorbed lutetium ions at 2~5BV (column volume) to obtain a concentrated lutetium chloride solution.

[0011] Furthermore, the method also includes ytterbium recovery, specifically: the ytterbium fraction is mixed with hydrochloric acid and then enters an ytterbium desalting column, ytterbium ions are adsorbed in the ytterbium desalting column, and then eluted with high-concentration hydrochloric acid in sequence to obtain a concentrated ytterbium chloride solution.

[0012] Furthermore, the method for recovering ytterbium specifically comprises: The strong cation exchange resin is loaded into the ytterbium-converted salt column as an adsorption filler; Pump deionized water into the ytterbium desalting column to completely replace the storage solution inside it; Add 0.1 mol / L to 12 mol / L hydrochloric acid or nitric acid to the ytterbium fraction to adjust its pH to 1 to 3, and mix the two evenly by gas stirring; The ytterbium fraction liquid is transported to the ytterbium desalting column by gas pressure or liquid infusion pump to provide power, and the ytterbium ions are adsorbed in the filler; Deionized water is pumped into the ytterbium desalting column for washing to remove residual organic carboxylic acids; 1 mol / L~6 mol / L hydrochloric acid is pumped into the ytterbium desalting column to elute the adsorbed ytterbium ions to obtain a concentrated ytterbium chloride solution.

[0013] Furthermore, the particle size of the polymer or silica gel matrix chromatographic filler in the separation column is 2 mm to 30 mm, the pore size is 2 Å to 100 Å, and the specific surface area is 50 m 2 / g~1000m 2 / g.

[0014] The polymer matrix chromatographic filler with sulfonic acid groups on the surface can be obtained by sulfonating polystyrene polymer microspheres, and the sulfonic acid group content is 0.6 to 2.0 mmol / g; The specific structure of the silica gel matrix chromatographic filler with sulfonic acid groups on the surface is as follows: ;

[0015] Wherein: the gray solid spheres in the formula represent silica gel particles; n=an integer of 0-10 (preferably 0-3), R is a phenyl group or a 2-hydroxyoxypropyl group, m=an integer of 0-10 (preferably 0-3); and the bonding amount of the sulfonic acid group is 0.2-2.0 mmol / g.

[0016] Furthermore, the matrix of the aminocarboxylic acid type chelating adsorbent in the lutetium desalting column is styrene-glycidyl acrylate copolymer, and its pore size is 20Å~300Å; the particle size is 10mm~100mm; the pore volume is 0.4cm 3 / g~1.5cm 3 / g; specific surface area is 50m 2 / g~300m 2 / g; the raw material for aminocarboxylic acid modification is selected from at least one or more of nitrilotriacetic acid, ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid, and the aminocarboxylic acid modification amount is 0.4 mmol / g~1.2mmol / g.

[0017] The present invention obtains high-concentration and high-purity lutetium chloride and / or ytterbium chloride through the steps of target material dissolution, ytterbium and lutetium separation, lutetium desalination concentration, ytterbium desalination recovery and the like.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses small-particle silica gel or polymer microspheres (2-30 mm) with uniform particle size distribution as the separation medium, which has significant advantages such as high column efficiency, large separation selectivity, and fast separation speed. A single separation column can achieve efficient preparation of trace amounts of lutetium-177, greatly shortening the separation time, reducing radiation loss, and greatly simplifying the separation process, making it easy to scale up.

[0019] 2. The present invention adopts aminocarboxylic acid type chelating adsorbent for post-desalting treatment of lutetium. After the filler realizes efficient adsorption of lutetium, lutetium can be eluted using dilute acid (0.05-0.5 M). The obtained highly concentrated LuCl3 solution can be directly used for radioactive labeling without evaporation post-treatment, which further reduces the design requirements of the plant, simplifies the production process, and shortens the production time.

[0020] 3. The present invention optimizes the four continuous steps of target dissolution, separation and purification, lutetium desalting and concentration, and ytterbium desalting and recovery. The whole process takes only 4 hours at the shortest. The purity of lutetium is greater than 98%, the yield is greater than 90%, and the recovery rate of the raw material ytterbium-176 is greater than 95%. Compared with the existing process, there is a significant improvement in production time. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the process device of the present invention; Illustration: 101-target dissolving tank, 102-sample tank; 201-heat exchanger, 202-six-way valve, 203-separation column, 204-first waste liquid tank, 205-ultraviolet detector, 206-energy spectrum detector, 207-lutetium liquid collecting tank, 208-ytterbium liquid collecting tank, 209-multi-way valve, 210-quantitative loop; 301-lutetium desalting column, 302-lutetium finished product tank, 303-second waste liquid tank, 304-energy spectrometer; 401-ytterbium desalting column, 402-ytterbium finished product tank, 403-third waste liquid tank; Figure 2 The chromatogram of the separation of ytterbium and lutetium obtained in Example 1; Figure 3 The PXRD comparison diagram of the Yb2O3 recovered in Example 1 and the purchased Yb2O3; Figure 4 The chromatogram of the separation of ytterbium and lutetium obtained in Example 2; Figure 5 The chromatogram of the separation of ytterbium and lutetium obtained in Example 3; Figure 6 The chromatogram of the separation of ytterbium and lutetium obtained in Example 4; Figure 7 The chromatogram is a separation diagram obtained by doping commercially available radioactive lutetium-177 into a natural mixture of ytterbium and lutetium; Figure 8 This is the TLC detection diagram of the radioactive labeling experiment of lutetium chloride. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] A preparation process of carrier-free lutetium-177, the method adopts Figure 1 The device shown includes steps S1 to S4.

[0024] The experiments carried out in the present invention are mainly cold experiments, using a mixture of naturally stable lutetium oxide and ytterbium oxide to simulate the composition of the target material after reactor irradiation, with a mass ratio of 4000:1.

[0025] S1. The ytterbium oxide-lutetium mixture obtained after reactor irradiation is used as a solid target material, and one or more strong acid solutions of 0.5 mol / L to 12 mol / L nitric acid, hydrochloric acid, sulfuric acid or hydrofluoric acid are added to completely dissolve it, and then the pH is adjusted to 0 to 3 to meet the requirements of chromatographic loading; In a specific implementation, the ytterbium oxide-lutetium mixture is placed in the target dissolving tank 101 of the device. An appropriate amount of one or more of nitric acid, hydrochloric acid, sulfuric acid or hydrofluoric acid is injected into the tank through the inlet of the tank cover, and the heating device is turned on to heat at a certain temperature for a period of time. After the solid target material is completely dissolved, the heating is stopped; then the dissolved target material solution to be separated is transferred to the sample tank 102 through the liquid outlet at the bottom of the target dissolving tank 101 by air pressure. Subsequently, a pH adjusting liquid such as an alkaline or buffer reagent is added to the target dissolving tank 101 in the same manner, and transferred to the sample tank 102, so as to adjust the pH and obtain the target material liquid to be treated; The advantage of transferring the target material dissolving solution and the pH adjusting solution separately is that the target dissolving tank 101 can be rinsed to reduce sample loss.

[0026] S2, using an organic carboxylic acid solution as a mobile phase, bringing the target liquid into a separation column to separate ytterbium ions and lutetium ions, thereby collecting and obtaining a lutetium fraction and an ytterbium fraction respectively; In the specific implementation, the separation and purification system used in this step mainly includes a heat exchanger 201, a six-way valve 202, a separation column 203, a first waste liquid tank 204, an ultraviolet detector 205, an energy spectrum detector 206, a lutetium liquid collection tank 207, an ytterbium liquid collection tank 208, a multi-way valve 209, and a quantitative ring 210, and is also equipped with corresponding pipelines, control valves, pump bodies, etc. The heat exchanger 201 is used to adjust the temperature of the mobile phase, and the two inlets of the six-way valve 202 are respectively connected to the outlet of the heat exchanger 201 and the outlet of the sample tank 102; the two inlets of the six-way valve 202 are connected to the outlet of the heat exchanger 201 and the outlet of the sample tank 102; The outlet is respectively connected to the upper end of the separation column 203 and the inlet of the first waste liquid tank 204; the six-way valve 202 also includes an inlet and an outlet connected to the quantitative ring 210 to form a circulation; the liquid from the separation column 203 is divided into two flow paths after flowing out, which are respectively connected to the ultraviolet detector 205 and the energy spectrum detector 206, and the liquid detected by the ultraviolet detector 205 enters the first waste liquid tank 204. According to different detection signals, the liquid detected by the energy spectrum detector 206 flows into the lutetium liquid collection tank 207, the ytterbium liquid collection tank 208 and the first waste liquid tank 204 respectively.

[0027] The separation column 203 is provided with sulfonic acid polymer or silica gel microspheres as the stationary phase, and specifically, the polymer or silica gel surface is modified with sulfonic acid groups. The particle size of the polymer or silica gel chromatographic filler is 2mm-30mm, the pore size is 2Å~100Å; the specific surface area is 50m 2 / g~1000m 2 / g.

[0028] The separation process of this step mainly includes two steps: system replacement balance and ytterbium-lutetium separation; The system replacement balance is performed before the formal ytterbium and lutetium separation, and the organic carboxylic acid is used as the mobile phase to flush the entire separation column 203. The flow path is as follows: the mobile phase is delivered by the pump, heated by the heat exchanger 201, and then enters any separation column 203 through the six-way valve 202. After flowing out of the separation column 203, it is divided into two flow paths; a small amount of branch (less than 3% of the total flow rate) flows into the ultraviolet detector 205 after reacting with the developer through the reaction tube, and is discharged into the first waste liquid tank 204 after detection, and is treated as waste liquid; the main flow path (>97%) flows through the energy spectrum detector 206, and is discharged into the first waste liquid tank 204 through the multi-way valve 209 after detection; the system replacement balance is to flush the separation column with the mobile phase so that the inside of the filler reaches a balanced state, and the temperature reaches the preset temperature; The flow path and equilibrium stage of the ytterbium-lutetium separation process are basically the same, with only one more sampling process; specifically: switch the six-way valve 202, pump the target liquid in the sample tank 102 into the quantitative ring 210, switch the six-way valve 202 again, the target liquid is brought into the separation column 203 by the mobile phase, and the separation process officially begins; the final destination of the main flow depends on the signals of the ultraviolet detector 205 and the energy spectrum detector 206; according to the signals provided by these two detectors, control the switching of the multi-way valve 209, when the lutetium signal is detected, it flows to the lutetium liquid collection tank 207; when the ytterbium signal is detected, it flows to the ytterbium liquid collection tank 208, and in other cases it flows to the first waste liquid tank 204; and there are several temperature sensors in the separation column 203 to monitor the temperature of the ytterbium-lutetium separation system at all times.

[0029] The eluent is an organic carboxylic acid commonly used in the art, including but not limited to at least one of lactic acid, α-hydroxyisobutyric acid, 2-hydroxy-2-methylbutyric acid, citric acid, ethylenediaminetetraacetic acid or their salts, and its concentration range is 0.01 mol / L to 0.6 mol / L; S3. After adjusting the pH of the lutetium fraction with hydrochloric acid or nitric acid, the lutetium fraction liquid is transferred to the lutetium desalting column by gas pressure loading or infusion pump, and the lutetium ions are adsorbed in the lutetium desalting column, and then eluted with dilute hydrochloric acid in sequence to obtain a concentrated lutetium chloride solution, which is carrier-free lutetium-177; The separated lutetium fraction contains organic carboxylic acid eluent and is very dilute, which does not meet the final use requirements. This step can not only remove the eluent and convert it into a lutetium chloride solution that meets medical use, but also achieve the concentration of the lutetium product.

[0030] In the specific implementation, the device used in this step mainly includes a lutetium desalting column 301, a lutetium finished product tank 302, a second waste liquid tank 303 and an energy spectrometer 304. The effluent of the lutetium desalting column 301 flows through the energy spectrometer 304 and is discharged into the second waste liquid tank 303 and the lutetium finished product tank 302. At the same time, corresponding pipelines, control valves, pump bodies, etc. are also provided; The lutetium desalting column 301 is provided with an aminocarboxylic acid type chelating adsorbent as a stationary phase.

[0031] The separation process of this step mainly includes system replacement, sample preparation, loading, washing and elution, including: (1) System replacement: Deionized water is pumped into the lutetium desalting column 301 to completely replace the storage solution inside it, and then it flows through the lutetium desalting column 301 and the spectrometer 304 and is discharged into the second waste liquid tank 303; (2) Sample preparation: Add 0.1 mol / L to 12 mol / L hydrochloric acid or nitric acid to the lutetium solution collection tank 207 to adjust the pH to between 1 and 3, and mix the mixture evenly by gas stirring; (3) Loading: The lutetium fraction solution in the lutetium solution collection tank 207 is transported to the lutetium desalting column 301 by gas pressure or liquid pumping, and the lutetium ions are adsorbed in the filler; (4) Washing: Deionized water is pumped into the lutetium desalting column to wash and remove the residual organic carboxylic acid, and then flows through the lutetium desalting column 301 and the spectrometer 304 and is discharged into the second waste liquid tank 303; (5) Elution: Pump 0.05-0.5 mol / L dilute hydrochloric acid into the lutetium desalting column to elute the adsorbed lutetium ions to obtain a concentrated lutetium chloride solution, i.e., carrier-free lutetium-177, which flows through the lutetium desalting column 301 and the energy spectrometer 304 and is discharged into the lutetium finished product tank 302.

[0032] S4, mixing the ytterbium fraction with hydrochloric acid or nitric acid and then entering an ytterbium desalting column, wherein the ytterbium ions are adsorbed in the ytterbium desalting column, and then sequentially eluting with dilute hydrochloric acid to obtain a concentrated ytterbium chloride solution; The separated ytterbium fraction contains organic carboxylic acid eluent, which is not conducive to the formation of precipitation. Therefore, the eluent can be removed through this step and converted into a concentrated ytterbium chloride solution, which is convenient for subsequent further precipitation and calcination into ytterbium oxide. The obtained ytterbium oxide can be recycled as a target material raw material.

[0033] In the specific implementation, the device used in this step mainly includes an ytterbium desalting column 401, an ytterbium finished product tank 402 and a third waste liquid tank 403, and is also equipped with corresponding pipelines, control valves, pump bodies, etc.; The ytterbium desalting column 401 is provided with a cation exchange resin as a stationary phase.

[0034] The ytterbium recovery process can be divided into several steps, including system replacement, sample preparation, loading, elution and elution, as follows: (1) System replacement: Deionized water is pumped into the ytterbium desalting column to completely replace the storage solution inside it, and then it flows through the ytterbium desalting column 401 and is discharged into the third waste liquid tank 403; (2) Sample preparation: Add 0.1 mol / L to 12 mol / L hydrochloric acid or nitric acid to the ytterbium liquid collection tank 208 to adjust the pH to between 1 and 3, and mix the two evenly by gas stirring; (3) Loading: The solution of the ytterbium fraction is transported to the ytterbium desalting column 401 by gas pressure or liquid pumping, and the ytterbium ions are adsorbed in the filler; (4) elution: deionized water is pumped into the ytterbium desalting column 401 to clean and remove the residual organic carboxylic acid, and then discharged into the third waste liquid tank 403 after passing through the ytterbium desalting column 401; (5) Elution: 1 mol / L to 8 mol / L hydrochloric acid is pumped into the ytterbium desalting column 401 to elute the adsorbed ytterbium ions to obtain a concentrated ytterbium chloride solution, which flows through the ytterbium desalting column 401 and is discharged into the ytterbium finished product tank 402.

[0035] Example 1

[0036] A preparation process of carrier-free lutetium-177, the method adopts Figure 1 The device shown comprises the following steps: Step 1, preparation of sulfonic acid silica gel: 1 kg of dried silica gel microspheres (average particle size 5 mm, pore size 100Å, specific surface area 340m 2 / g) was dispersed in 5L xylene, 0.2 kg 2-(4-phenylsulfonyl chloride)ethyltrichlorosilane was added, heated to 110℃, and reacted for 16 hours. After the reaction, the temperature was cooled to below 50℃, filtered, washed with xylene and methanol in turn, and dried. Then the sulfonyl chloride group was hydrolyzed, and the washed filler was added to 5L 5wt% sodium bicarbonate aqueous solution, stirred at room temperature for 16 hours, filtered, washed with water and methanol in turn, and placed in a vacuum drying oven after drying at 80℃ for 12 hours. The surface sulfonic acid group bonding density of the obtained sulfonic acid silica gel filler was about 0.4mmol / g.

[0037] The silica microspheres with the following schematic structure were obtained: ;

[0038] Step 2, high-efficiency separation chromatographic column filling: high-efficiency separation chromatographic column (inner diameter 50 mm, column length 250 mm), weigh 320g of sulfonic acid silica gel filler obtained in the above step 1, use methanol as the homogenization solvent, evenly disperse the filler in the homogenization solvent to obtain a homogenate, then quickly pour the homogenate into the column tube of the chromatographic column, and compress it with a column packing machine. The column filling pressure is 10Mpa. When the homogenization solvent is completely discharged from the column tube, the column filling is completed, and its column efficiency is greater than 80,000 / m, and a separation column is obtained.

[0039] Step 3, target dissolution: Use stable ytterbium oxide-lutetium oxide to simulate the composition of the target material after irradiation, weigh 100 mg of ytterbium oxide and 25 mg of lutetium oxide and mix them evenly, with a mass ratio of 4000:1, add 8 mL of 2M nitric acid solution, heat to 80°C to completely dissolve it, and then use 1 M ammonia water to adjust the pH to 0.5 to meet the chromatographic loading requirements, and obtain the simulated dissolved solution of the target material to be separated.

[0040] Step 4, efficient separation of lutetium and ytterbium: use 30 mmol / L a-hydroxyisobutyric acid (25-28 wt.% concentrated ammonia water adjusted to pH 4.5) aqueous solution as mobile phase, flow rate is 60 mL / min, first use 2 BV mobile phase to wash and elute the entire separation column, so that the separation column reaches equilibrium; inject the target material solution into the quantitative loop through the injector, and then use the mobile phase to bring the target material liquid in the quantitative loop into the separation column, and control the switching of the multi-way valve according to the signal provided by the ultraviolet detector. When the lutetium signal is detected, it flows to the lutetium liquid collection tank, which is the lutetium fraction; when the ytterbium signal is detected, it flows to the ytterbium liquid collection tank, which is the ytterbium fraction. In other cases (when there is no ultraviolet signal of lutetium and ytterbium), it flows to the first waste liquid tank. Its chromatogram is as shown below. Figure 2 As shown, the separation process took only 1 hour.

[0041] Step 5, preparation of stationary phase of lutetium desalting column: 30 mL 1-bromododecane, 8 mL glycidyl methacrylate, 30 mL acrylamide, 0.4 g azobisisobutyronitrile were mixed evenly, and the oil phase and 1 L aqueous phase containing 4 g polyvinyl alcohol and 19.5 g sodium carbonate were mixed evenly. Stir at 800 rpm, emulsify for 30 min, raise the temperature to 65 ° C, and react for 4 h. The pore size of the obtained polymer microspheres is 120 Å; the particle size is 30 mm; the pore volume is 0.7 cm 3 / g; specific surface area is 180 m 2 / g; 10 g of the above polymer microspheres, 5 g of nitrilotriacetic acid and 6 g of sodium bicarbonate were added to 150 mL of N,N-dimethylformamide, heated and stirred at 90°C for 24 hours, filtered, washed with methanol, 0.2 M hydrochloric acid solution and water in sequence, and the obtained solid was vacuum dried in a drying oven at 60°C for 16 hours to obtain a polymer material modified with nitrilotriacetic acid NTA. The modification amount of nitrilotriacetic acid NTA was 0.7 mmol / g; The polymer microspheres with the following schematic structure are obtained: ; The above polymer microspheres were loaded into a PEEK chromatographic column with an inner diameter of 4.6 mm and a length of 100 mm as a lutetium desalting column for the desalting and concentration of lutetium.

[0042] Step 6, lutetium desalting and concentration: before use, use 5BV of deionized water to completely replace the storage solution in the lutetium desalting column; add 2mol / L hydrochloric acid to the lutetium solution collection tank, adjust the pH of the lutetium fraction to 1, and stir the lutetium fraction and the hydrochloric acid by nitrogen bubbling to evenly mix the lutetium fraction and the hydrochloric acid to form a lutetium acid solution; use high-purity nitrogen to pressurize the material to transport the lutetium acid solution to the lutetium desalting column, and the lutetium ions are adsorbed in the aminocarboxylic acid type chelating adsorption filler; pump 20BV of deionized water into the lutetium desalting column for washing and removing residual organic carboxylic acids; pump 0.1mmol / L dilute hydrochloric acid (3BV) into the lutetium desalting column to elute the adsorbed lutetium ions to obtain a concentrated lutetium chloride solution, which is carrier-free lutetium-177.

[0043] Step 7, ytterbium desalting and concentration: a strong cation exchange resin (DOWEX® 50WX8 cation exchange resin) is filled in an ytterbium desalting column (PEEK chromatographic column with an inner diameter of 20 mm and a length of 150 mm). Before use, all the storage solution inside is replaced with 3BV deionized water; 2 mol / L hydrochloric acid is added to the ytterbium solution collection tank, the pH of the ytterbium fraction is adjusted to 1, and the ytterbium fraction and the hydrochloric acid are mixed evenly by nitrogen bubbling and stirring; the solution of the ytterbium fraction is transported to the ytterbium desalting column by high-purity nitrogen pressure, and the ytterbium ions are adsorbed in the filler; 3BV deionized water is pumped into the ytterbium desalting column for cleaning to remove residual organic carboxylic acids; 3BV4 M hydrochloric acid is pumped into the ytterbium desalting column to elute the adsorbed ytterbium ions to obtain a concentrated ytterbium chloride hydrochloric acid solution.

[0044] Step 8. The concentrated ytterbium chloride hydrochloric acid solution is adjusted to pH 1.5 with 25-28 wt.% concentrated ammonia, and then 0.1 M oxalic acid solution is added, the molar amount of which is 10 times that of ytterbium, to obtain ytterbium oxalate precipitate, and then filtered to obtain ytterbium oxalate solid. The obtained precipitate is transferred to a crucible and calcined at 850°C in a muffle furnace for 2 hours to obtain 98.3 mg Yb2O3 with a recovery rate of 98.3%. It is compared with the powder X-ray diffraction spectrum of the purchased Yb2O3 (Aladdin, 99.99% metals basis, CAS: 1314-37-0). Figure 3 As shown, no impurity peaks were observed, confirming that high-purity ytterbium oxide powder was recovered.

[0045] Example 2

[0046] Based on Example 1, the process and conditions are the same as Example 1, except that: Step 1, preparation of sulfonic acid silica gel: 1 kg of dried silica gel microspheres (average particle size 5 mm, pore size 100 Å, specific surface area 340 m 2 / g) was dispersed in 5L xylene, 1.5L 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added, heated to 110℃, and reacted for 16 hours. After the reaction, the temperature was lowered to below 50℃, filtered, washed with xylene and methanol in turn, dried in a vacuum oven at 80℃, and dried for 12 hours to prepare epoxy silica gel. 1 kg sodium bisulfite was mixed with 10L water, stirred until completely dissolved, and then added to the above epoxy silica gel, reacted at 85℃ for 24 hours, filtered, washed with water and methanol in turn, dried in a vacuum oven at 80℃, and dried for 12 hours. The surface sulfonic acid group bonding density of the obtained sulfonic acid silica gel filler was about 0.4 mmol / g.

[0047] The silica microspheres with the following structure were obtained: ; Step 4: Efficient separation of ytterbium and lutetium: The obtained separation spectrum is as follows: Figure 4 shown.

[0048] Example 3 Based on Example 1, the process and conditions are the same as Example 1, except that: In step 3, target dissolution: Stable ytterbium oxide-lutetium oxide simulates the composition of the target material after irradiation. Weigh 200 mg of ytterbium oxide and 50 mg of lutetium oxide and mix them evenly. Add 16 mL of 1.5 M nitric acid solution and heat to 100°C to completely dissolve them. Then use 1 M ammonia water to adjust the pH to 0.2 to meet the chromatographic loading requirements.

[0049] Efficient separation of ytterbium and lutetium in step 4: Replace the elution conditions in step 4 with a 40 mmol / L 2-hydroxy-2-methylbutyric acid (pH adjusted to 4.4 with ammonia) aqueous solution as the mobile phase at an elution flow rate of 45 mL / min.

[0050] The lutetium-ytterbium separation chromatogram obtained in this example is as follows Figure 5 As shown in the figure, as the processing amount increases to 200 mg, the tailing of the ytterbium chromatographic peak becomes longer and the separation time increases to 90 min.

[0051] The other steps and reaction conditions are the same as those in Example 1.

[0052] Example 4

[0053] Based on Example 1, the process and conditions are the same as Example 1, except that: The 5 mm sulfonic acid silica microspheres in the separation column were adjusted to sulfonic acid polymer microspheres with an average particle size of 10 mm (particle size range 7-16 mm). The synthesis process (i.e., step 1) is as follows: 24 g of polyethylene glycol mono-4-nonylphenyl ether n≈5, 93.6 g of sodium chloride, 3.2 L of 10% gelatin aqueous solution and 8 L of pure water were placed in a 20 L three-necked flask and stirred at 600 rpm to obtain the aqueous phase; the oil phase containing 275.8 g of divinylbenzene, 200.2 g of n-heptane, 167.8 g of xylene and 10.5 g of azobisisoheptanonitrile was mixed evenly, and then mixed with the aqueous phase, the temperature was raised to 65 ° C, and the reaction was carried out for 6 hours. Washed with water and ethanol three times respectively, and vacuum dried to obtain 700 mL of polymer microspheres. The pore size of the polymer microspheres is 50-100 Å; the particle size is 7-15 mm, the average particle size is 10 mm; the pore volume is 1.5 cm 3 / g; specific surface area is 789 m 2 / g. The above 500 mL polystyrene microspheres (average particle size 10 mm) were mixed evenly with 5.5 kg of 98% concentrated sulfuric acid, stirred at 200 rpm, and reacted at 0°C for 24 hours. The microspheres were washed with water and ethanol respectively until neutral, and vacuum dried to obtain sulfonic acid group-modified polymer microspheres. The sulfonic acid group ion exchange capacity of the polymer microspheres was 1.62 mmol / g.

[0054] Target dissolution in step 3: Stable ytterbium oxide-lutetium oxide simulates the composition of the target material after irradiation. Weigh 300 mg of ytterbium oxide and 75 mg of lutetium oxide and mix them evenly. Add 20 mL of 1.5 M nitric acid solution and heat to 120°C to completely dissolve them. Then use 1 M ammonia water to adjust the pH to 0.2 to meet the chromatographic loading requirements.

[0055] Efficient separation of ytterbium and lutetium in step 4: Using 50 mmol / L a-hydroxyisobutyric acid (28 wt.% ammonia adjusted to pH 4.48) aqueous solution as the mobile phase, the flow rate is 50 mL / min. The lutetium-ytterbium separation chromatogram obtained in this example is as follows: Figure 6 As shown, the processing amount was increased to 300 mg, and the separation time was further increased to 100 min due to the tailing of ytterbium.

[0056] Step 6 Lutetium desalting and concentration: The aminocarboxylic acid complexing agent for polymer surface modification is diethylenetriaminepentaacetic acid (DPTA), and the other reaction conditions are the same as those in Example 1; the modification amount of DTPA is 0.9 mmol / g, and the hydrochloric acid concentration is increased to 0.4 M in the elution step.

[0057] Example 5

[0058] Based on Example 1, the process and conditions are the same as Example 1, except that: In step 4, silica microspheres with an average particle size of 30 mm and a pore size of 100 Å were used; the specific surface area was 323 m 2 / g; Efficient separation of ytterbium and lutetium in step 4: Replace the elution conditions in step 4 with 70 mmol / L lactic acid (pH adjusted to 4.7 with aqueous ammonia) as the mobile phase at a flow rate of 55 mL / min.

[0059] Step 6 Lutetium desalting and concentration: The aminocarboxylic acid complexing agent for polymer surface modification was replaced with ethylenediaminetetraacetic acid (EDTA), and the other reaction conditions were the same as those in Example 1. The modification amount of EDTA was 0.7 mmol / g. In the elution step, the hydrochloric acid concentration was increased to 0.5 M.

[0060] Example 6

[0061] Based on Example 1, the process and conditions are the same as Example 1, except that: The particle size range of the sulfonic acid polymer microspheres in the separation column is adjusted to 20-40 mm, with an average particle size of 30 mm. The synthesis process (i.e., step 1) is as follows; 80 g PVA-1788, 42 g sodium dodecyl sulfate, and 116.8 g sodium chloride were dispersed in 8 L pure water, placed in a 20 L three-necked flask, and stirred at 400 rpm until clear to obtain the aqueous phase; the oil phase containing 275.8 g divinylbenzene, 200.2 g n-heptane, 167.8 g xylene, and 10.5 g azobisisoheptonitrile was mixed evenly, and then mixed with the aqueous phase, and the temperature was raised to 65 ° C and reacted for 6 hours. Washed with water and ethanol three times in turn, and vacuum dried to obtain polymer microspheres. The pore size of the polymer microspheres is 50-100 Å; the particle size range is 20~40 mm, the average particle size is 30 mm; the pore volume is 1.43 cm 3 / g; specific surface area is 712 m 2 / g. The above 500 mL polystyrene microspheres were mixed evenly with 5.5 kg of 98% concentrated sulfuric acid, stirred at 200 rpm, and reacted at 0°C for 24 hours. The microspheres were washed with water and ethanol respectively until neutral, and vacuum dried to obtain sulfonic acid group-modified polymer microspheres. The sulfonic acid group ion exchange capacity of the polymer microspheres was 1.58 mmol / g.

[0062] Efficient separation of ytterbium and lutetium in step 4: Replace the elution conditions in step 4 with 35 mmol / L citric acid (pH adjusted to 3.7 with ammonia) aqueous solution as the mobile phase at an elution flow rate of 55 mL / min.

[0063] Preparation of lutetium desalting adsorption material in step 5: The aminocarboxylic acid complexing agent for polymer surface modification is replaced with ethylenediaminetetraacetic acid (EDTA), and the other reaction conditions are the same as those in Example 1. The modification amount of EDTA is 0.7 mmol / g. In the elution step, the hydrochloric acid concentration is increased to 0.5 M.

[0064] Comparative Example 1 Based on Example 1, the process and conditions are the same as Example 1, except that; The sulfonic acid groups modified on the surface of the silica gel in the separation chromatographic column are replaced with carboxylic acid groups. The specific synthesis process is as follows: 1 kg of dried silica microspheres (average particle size 5 mm, pore size 100Å, specific surface area 340 m 2 / g) was dispersed in 5L xylene, 1.0L cyanopropyltrichlorosilane was added, heated to 110℃, and reacted for 24h. After the reaction, the temperature was lowered to below 50℃, filtered, washed with xylene and methanol in turn, dried in a vacuum oven at 80℃, and dried for 12h to prepare cyano-modified silica gel. The cyano-modified silica gel was further dispersed in 10L 0.1mol / L hydrochloric acid water, reacted at 90℃ for 24h, filtered, washed with water and methanol in turn, dried in a vacuum oven at 80℃, and dried for 12h. The surface carboxyl bonding density of the obtained carboxyl silica gel filler was about 0.5 mmol / g.

[0065] The silica microspheres with the following structure were obtained: ; Step 4: Efficient separation of lutetium and ytterbium: The elution conditions in Examples 1-6 were used respectively. It was found that the carboxyl group as the surface modification group of the stationary phase could not achieve effective separation of lutetium and ytterbium.

[0066] Comparative Example 2 Based on Example 1, the process and conditions are the same as Example 1, except that; Step 5, lutetium desalting column preparation: A strong cation exchange resin (DOWEX® 50WX8 cation exchange resin) is filled in the lutetium desalting column (PEEK column with an inner diameter of 4.6 mm and a length of 100 mm). After eluting 10BV with 2M hydrochloric acid, the lutetium ion recovery rate is only 63%. Due to the large elution volume, the product concentration is relatively dilute and does not meet the use requirements; after eluting 4BV with 4M hydrochloric acid, the lutetium ion recovery rate is greater than 90%, but further evaporation is required to completely remove the 4M hydrochloric acid in order to meet the subsequent radioactive drug labeling requirements. Due to the strong corrosiveness of hydrochloric acid, high requirements are placed on plant equipment. It is necessary to select production equipment that is resistant to hydrochloric acid corrosion and build efficient ventilation facilities. In addition, the evaporation step further increases the total processing time and increases radioactive losses.

[0067] The lutetium chloride and ytterbium chloride concentrates prepared in Examples 1 to 6 were subjected to elemental analysis tests using ICP-MS or ICP-OES. The results are shown in Table 1 below.

[0068] Table 1 is the element analysis test of Examples 1 to 6

[0069] As can be seen from the data in Table 1, Examples 1 to 6 of the present invention produce high-purity carrier-free lutetium-177 with high yield, and the organic carboxylic acid in the lutetium fraction is effectively removed by the lutetium desalting and concentration system, and the lutetium chloride can be eluted by dilute hydrochloric acid, and the concentration of lutetium chloride is effectively increased to produce carrier-free lutetium-177 that meets medical requirements. In combination with the ytterbium desalting column, high-purity ytterbium chloride is recovered, and efficient recovery of the target material is achieved, further reducing production costs.

[0070] In Examples 1 to 3, stable ytterbium and lutetium solutions were used as simulated solutions for chromatographic separation and purification. The obtained chromatograms are shown in FIG. Figures 3 to 5 As shown, it only has UV signal.

[0071] The radioactive lutetium-177 purchased from the market was doped into a natural ytterbium and lutetium mixture, and the ratio of radioactive lutetium-177 to stable lutetium was 1:17.7. According to the conditions of Example 1, the separation spectrum obtained was as follows: Figure 7 As shown, there are both radioactive signals and ultraviolet signals. Radioactive isotopes and stable isotopes of the same element have the same chemical properties, so it is completely scientific and reasonable to use stable isotopes instead of radioactive isotopes to develop process flows. Moreover, the separation experiment was repeated many times using samples doped with radioactive lutetium-177, and no changes in the spectrum were observed, indicating that the separation material used in the process of the present invention has good radiation resistance. The obtained lutetium chloride (containing radioactive lutetium-177) solution was subjected to a radioactive labeling experiment, and the labeled molecule was DOTA. Finally, it was detected by iTLC, as shown in FIG. Figure 8 As shown, the labeling rate of lutetium is 95.9%.

[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A process for preparing carrier-free lutetium-177, characterized in that: The preparation process comprises the following steps: The raw material to be separated and purified is a target material solution to be separated containing lutetium and ytterbium elements and having a pH value of less than or equal to 3; A chromatographic separation column is used for separation, an organic carboxylic acid solution is used as a mobile phase, and a chromatographic filler with a sulfonic acid group modified on the surface is used as a stationary phase, the target material solution to be separated is loaded into the separation column, and liquid chromatography is performed to separate the lutetium fraction and the ytterbium fraction; The pH value of the lutetium fraction is adjusted to 1-3 to obtain a lutetium acid solution; The lutetium acid solution is injected into a lutetium desalting column, lutetium ions are adsorbed in the lutetium desalting column, and then eluted with dilute hydrochloric acid in sequence to obtain a concentrated lutetium chloride solution of lutetium-177; the lutetium desalting column is a chromatographic column using an aminocarboxylic acid type chelating agent as a stationary phase.

2. The process for preparing carrier-free lutetium-177 according to claim 1, characterized in that: The specific operation of separating the lutetium fraction and the ytterbium fraction by liquid chromatography is as follows: First, the separation column is flushed with the mobile phase to allow the packing to reach an equilibrium state; Inject the target material solution to be separated into the quantitative loop through the injector; The target material solution to be separated in the quantitative loop enters the separation column driven by the mobile phase and starts to separate, and the lutetium fraction and the ytterbium fraction flowing out of the separation column are respectively collected by detecting signals through an energy spectrum detector and / or an ultraviolet detector; The organic carboxylic acid is selected from at least one or more of lactic acid, α-hydroxyisobutyric acid, 2-hydroxy-2-methylbutyric acid, citric acid, ethylenediaminetetraacetic acid or their salts, and the concentration range of the organic carboxylic acid solution is 0.01 mol / L to 0.6 mol / L.

3. The process for preparing carrier-free lutetium-177 according to claim 1, characterized in that: The preparation method of the target material solution to be separated is as follows: using the ytterbium oxide-lutetium mixture obtained after reactor irradiation as a solid target material, adding one or more strong acid solutions of 0.5 mol / L to 12 mol / L nitric acid, hydrochloric acid, sulfuric acid or hydrofluoric acid to completely dissolve it, adjusting the pH to 0 to 3 to meet the chromatographic loading requirements, and preparing a mixture of ytterbium ions and lutetium ions as the target material solution to be separated.

4. The process for preparing carrier-free lutetium-177 according to claim 1, characterized in that: The specific steps of obtaining a concentrated lutetium chloride solution include: Pumping water into the lutetium desalting column to completely replace the solution inside the column; Add 0.1 mol / L to 12 mol / L hydrochloric acid or nitric acid to the lutetium fraction to adjust its pH to 1 to 3, and mix the two evenly by gas stirring; The lutetium fraction is transported to the lutetium desalting column by gas pressure or liquid pumping, and the lutetium ions are adsorbed in the filler; Water is pumped into the lutetium desalting column for washing to remove residual organic carboxylic acids; Pump 0.05mol / L~0.5mol / L dilute hydrochloric acid into the lutetium desalting column, elute the adsorbed lutetium ions for 2-5 BV, and obtain a concentrated lutetium chloride solution.

5. The process for preparing carrier-free lutetium-177 according to claim 1, characterized in that: The preparation process also includes ytterbium recovery, specifically: the ytterbium fraction is mixed with 0.1 mol / L to 12 mol / L hydrochloric acid or nitric acid and then enters an ytterbium desalting column, ytterbium ions are adsorbed in the ytterbium desalting column, and then eluted with high-concentration hydrochloric acid in sequence to obtain a concentrated ytterbium chloride solution; The methods for ytterbium recovery specifically include: A strong cation exchange resin is loaded into an ytterbium desalting column as an adsorption filler; Pump water into the ytterbium desalting column to completely replace the storage solution inside it; Add 0.1 mol / L to 12 mol / L hydrochloric acid or nitric acid to the ytterbium fraction to adjust its pH to 1 to 3, and mix the two evenly by gas stirring; The ytterbium fraction liquid is transported to the ytterbium desalting column by gas pressure or liquid infusion pump, and the ytterbium ions are adsorbed in the filler; Deionized water is pumped into the ytterbium desalting column for washing to remove residual organic carboxylic acids; 1 mol / L~6 mol / L hydrochloric acid is pumped into the ytterbium desalting column to elute the adsorbed ytterbium ions to obtain a concentrated ytterbium chloride solution.

6. The process for preparing carrier-free lutetium-177 according to claim 1 or 2, characterized in that: The particle size of the polymer or silica-based microspheres in the separation column is 2 mm to 30 mm, the pore size is 2 Å to 100 Å, and the specific surface area is 50 m 2 / g~1000m 2 / g.

7. The process for preparing carrier-free lutetium-177 according to claim 1 or 4, characterized in that: The modification raw material of the aminocarboxylic acid type chelating adsorbent in the lutetium desalting column is selected from at least one or more of nitrilotriacetic acid, ethylenediaminetetraacetic acid and diethylenetriaminepentaacetic acid.

8. The process for preparing carrier-free lutetium-177 according to claim 1 or 4, characterized in that: The matrix of the aminocarboxylic acid chelating adsorbent in the lutetium desalting column is styrene-glycidyl acrylate copolymer, with a pore size of 20Å~300Å; a particle size of 10mm~100mm; and a pore volume of 0.4cm 3 / g~1.5cm 3 / g; specific surface area is 50m 2 / g~300m 2 / g; the raw material for aminocarboxylic acid modification is selected from at least one or more of nitrilotriacetic acid, ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid, and the aminocarboxylic acid modification amount is 0.4 mmol / g~1.2 mmol / g.

9. The process for preparing carrier-free lutetium-177 according to claim 5, characterized in that: The strong cation exchange resin in the ytterbium desalting column is obtained by sulfonation of polystyrene polymer microspheres. The sulfonic acid group modification amount is 0.6 mmol / g~4 mmol / g, and the pore size is 20Å~300Å; the particle size is 10mm~300mm, and the specific surface area is 50m 2 / g~800m 2 / g.

10. The process for preparing carrier-free lutetium-177 according to claim 1, characterized in that: The preparation process comprises the following steps: The raw material to be separated and purified is a target material solution to be separated containing lutetium and ytterbium elements and having a pH value of less than or equal to 3; A chromatographic separation column is used for separation, an organic carboxylic acid solution is used as a mobile phase, and a chromatographic filler with a sulfonic acid group modified on the surface is used as a stationary phase, the target material solution to be separated is loaded into the separation column, and liquid chromatography is performed to separate the lutetium fraction and the ytterbium fraction; The concentrated lutetium chloride solution is obtained by: adjusting the pH value of the lutetium fraction to 1-3 to obtain a lutetium acid solution; The lutetium acid solution is injected into a lutetium desalting column, lutetium ions are adsorbed in the lutetium desalting column, and then eluted with dilute hydrochloric acid in sequence to obtain a concentrated lutetium chloride solution of lutetium-177; the lutetium desalting column is a chromatographic column with an aminocarboxylic acid type chelating agent as a stationary phase; The concentrated ytterbium chloride solution is obtained by mixing the ytterbium fraction with 0.1 mol / L to 12 mol / L hydrochloric acid or nitric acid and then entering an ytterbium desalting column, where ytterbium ions are adsorbed in the ytterbium desalting column, followed by sequential elution with elution and high-concentration hydrochloric acid to obtain a concentrated ytterbium chloride solution.

Citation Information

Patent Citations

  • Method for producing carrier-free highly pure 177lu compounds and carrier-free 177lu compounds

    CN103718250A

  • Separation and purification method of carrier-free lutetium 177

    CN118668079A

  • Method for separating and purifying lutetium from ytterbium and lutetium mixture

    CN115216652A

  • Method for separating and preparing uranium and lanthanide from uranium and lanthanide mixture

    CN117845052A

  • Method for the cation-exchange extraction of the radionuclide lutetium-177

    WO2022255905A1